Relationship Between Donor Graft Area And Area Of Surgical Repigmentation - Lahiri Koushik; Sengupta S.R (Wolters Kluwer Medknow Publications, 1999)
A total of 1742 grafts were placed over 177 lesions on 29 regions in 110 individuals with stable cutaneous achromia. Sixty-seven of them were female and forty-three male. Age ranged between 6 and 71 years. Cases were followed up to a maximum period of 2 years. The extent of maximum pigment spread (MPS) ranged between 0 and 10 mm, with an overall average of approximately 5.5mm. Based on this finding, it was calculated that from a 2mm donor graft an average of 132.66 mm2 areas is regimented which is almost 42 times larger than the area of the graft itself.